Post-tuberculosis health-related quality of life, lung function and exercise capacity in a cured pulmonary tuberculosis population in the Breede Valley District, South Africa - Kurt J. Daniels; Elvis Irusen; Hamilton Pharaoh; Susan Hanekom (AOSIS, 2019)
Background: Pulmonary tuberculosis (PTB) remains a major concern worldwide. Albeit curable, PTB continues to negatively affect patients' health-related quality of life (HRQoL) and functioning even after cure. Objectives: To describe the demographics, respiratory symptoms, pulmonary airflow patterns, HRQoL and exercise capacity of cured PTB patients, in the Breede Valley district of South Africa. Methods: A cross-sectional study conducted at five primary health care facilities included adult patients diagnosed with PTB, who had completed anti-tuberculosis treatment. Post-treatment bronchodilator lung function, HRQoL and 6-min walk distance (6MWD) were measured. Results: Three hundred and twenty-four patients were screened. Specific challenges resulted in 45 patients being included (male n = 25 [56%]; mean population age 39.9 [± 10.2]). HRQoL was assessed using the short-form 12v2, part of the burden of lung disease core questionnaire. In general, self-reported physical scores (physical health component summary score = 45) were higher than mental scores (mental health component summary score = 39). The mean 6MWD was 294.5 m (± 122.7) m (range 110 m - 600 m), which is well below normal reference values. Forty-eight percent (48%) of the sample presented with abnormal lung function, including obstructive (n = 9; 21%), restrictive (n = 11; 25%) and mixed (n = 1; 2%). Conclusions: This pilot study suggests that most cured PTB patients have decreased HRQoL, exercise capacity and abnormal lung function. This study is the first to describe the combination of these three outcomes in a South African population. Clinical implications: Clinicians must recognise that holistic management of PTB patients is required after cure.